In vitro evaluation of Malaysian Natural coral Porites bone graft substitutes (CORAGRAF) for bone tissue engineering: a preliminary study - AL-Salihi, K. A. (2015)
Aim: An approach for three-dimensional (3D) bone tissue generation from bone marrow mesenchymal adult stem cells (BMSC-AS) was investigated. Methods: The BMSC-AS cells were induced to differentiate into osteogenic precursors, capable of proliferating, and subsequently differentiating into bone-forming cells. The differentiated cells were seeded on the surface of coral discs with a mean diameter 10 (±2) mm and a mean thickness 1 (±0.5) mm. The seeded scaffolds were characterized using von Kossa and Alizarin Red staining, electron and confocal microscopy and RT-PCR analysis. Results: The results demonstrated that BMSC-AS derived bone-forming cells attached to and colonized into coral scaffolds. Furthermore, these cells produced bone nodules when grown for 3-4 weeks in mineralization medium containing ascorbic acid and beta-glycerophosphate both in tissue culture plates and in scaffolds. The differentiated cells also expressed osteospecific markers when grown both in the culture plates and in 3D scaffolds. Osteogenic cells expressed alkaline phosphatase, osteocalcin, and osteopontin, but not a BMSC-AS cell-specific marker, oct-4. Conclusion: These findings suggest that Malaysian Natural coral Porites bone graft substitutes (CORAGRAF) with BMSC-AS cells can be used for in vitro tissue engineering to cultivation of graftable skeletal structures.